Fascist modernities : Italy, 1922-1945 - Ben-Ghiat, Ruth (Studies on the history of society and culture, 2001)
This cultural history of Mussolini's dictatorship discusses the meanings of modernity in interwar Italy. The work argues that fascism appealed to many Italian intellectuals as a new model of modernity that would resolve the European and national crises.